The Contribution of Different Femur Segments to Overall Femoral Torsion. (July 2016) - Seitlinger, Gerd; Moroder, Philipp; Scheurecker, Georg; Hofmann, Siegfried; Grelsamer, Ronald P.
Background: Femoral torsion is a critical parameter in hip and knee disorders. The unproven assumption is that the femoral neck exclusively contributes to the overall torsion of the femur. Purpose/Hypothesis: The aim of this study was to measure femoral torsion at different levels in patients with abnormally high or low femoral torsion and to compare the results with healthy volunteers. Our hypothesis was that the pattern of torsion distribution among the different femoral levels varies between patients with abnormal torsion and healthy volunteers. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Magnetic resonance images of patients with a history of patellar instability and torsion of the femur ≥25° (11 patients, 16 femurs) and ≤0° (14 patients, 22 femurs) were analyzed. Our controls were 30 healthy volunteers (60 femurs). To assess femoral torsion, 4 lines were drawn: a first line through the center of the femoral head and neck, a second line through the center of the femur at the top of the lesser trochanter, a third line tangent to the posterior aspect of the distal femur just above the attachment of the gastrocnemius, and a fourth line tangent to the posterior condyles. Three investigators performed the measurements; 1 performed the measurements twice. Results: All femur segments showed significantly different torsion among the high-torsion, low-torsion, and control groups. Regarding the pattern of torsion distribution, on average, all levels contributed to the torsion. The ratio between the average neck and shaft torsion shifted toward a higher value in the high-torsion group, mostly because of a lack of external torsion in the shaft, and toward a lower value in the low-torsion group, owing to both a lack of internal torsion of the neck and increased external torsion in the shaft. Conclusion: We established a difference between neck, mid, and distal femoral torsion with reproducible measurements. Our data suggest that all 3 levels of the femur contribute to the total femoral torsion, with a different pattern among patients with high torsion and patellar instability.